‘Sink or swim?’: Learning from stories of becoming academics within a transforming university terrain - Pithouse-Morgan, K; Naicker, I; Pillay, D; Masinga, L; Hlao, T (South African Journal of Higher Education, 2016)
The meanings connected with becoming or being an academic are constantly shifting, on account of diverse forces that act on universities. The authors of this article portray their learning as a research team of four academics (including one early-career academic) and a doctoral student who took a narrative inquiry approach to listening and responding to their early-career colleagues’ stories of becoming and being academics within a transforming university landscape. Imaginative engagement with these stories through the evocative and reflexive medium of poetry awakened possibilities for navigating the uncertain terrain of academia. The article draws attention to collegial relationships as critical to the growth of self-belief and self-resourcefulness in becoming and being academics. It demonstrates how, through collective participation, novice and experienced academics can become valuable sources of learning and support for each other.